Exploring the Use of Augmentative and Alternative Communication with Emergent Literacy Learners - Cheyenne Kopinsky (Canadian Society for Studies in Education, 2022)
Augmentative and alternative communication (AAC) has the opportunity to transform the lives of individuals with complex communication needs (CCN). For neurodivergent learners who use AAC to communicate, their acquisition of language and literacy is often dependent on the tools they use and the amount of support and intervention they receive. Through the analysis of twenty-two studies, risks of delayed language development, use of AAC with emergent literacy learners, and implications for classroom context are explored. Although results indicate that AAC can benefit neurodivergent students in their acquisition of language and literacy, further research is needed to completely understand the value AAC brings to neurodivergent individuals with complex communication needs.